Systematic academic instruction for students with EBD: the construction and use of a tool for teachers. Issue 1 (23rd February 2015) - van der Worp‐van der Kamp, Lidy; Pijl, Sip Jan; Post, Wendy J.; Bijstra, Jan O.; van den Bosch, Els J.
Abstract : Educating students with behavioural, emotional and social difficulties requires a thorough systematic approach with the focus on academic instruction. This study addresses the development of a tool, consisting of two questionnaires, for measuring systematic academic instruction. The questionnaires cover the Plan‐Do‐Check‐Act cycle and academic versus behavioural instruction. The questionnaires are both practically oriented as well as theoretically well founded. The reliability turned out to be acceptable (0.76) to high (0.89). Observation scales were developed to determine the validity of both questionnaires. Moderate correlations between questionnaires and observation scales were found (0.31, 0.32). Bland–Altman plots offered us valuable information about the differences between questionnaires and observation scales, supplying us with important issues for further research. It is concluded that the questionnaires might be a valuable tool for assessing teachers' systematic academic instruction.